Instrumentalization of obstetric nursing residents about preparing women for childbirth: an integrative review (Research, Society and Development, 2020)
The present study has as main objective to survey in scientific literature the activities developed in the training of residents in obstetric nursing about the instrumentalization for the performance in education for childbirth and birth and; Identify assertive and rebuttal points in the training of residents in obstetric nursing about instrumentalization to work in education for childbirth and birth. Integrative Review. The search of articles occurred by literature survey at BVS, LILACS, BDEnf, MEDLINE and SCIELO, published productions in Portuguese and English, with full text avaiable, period from 2015 to 2019 and which are related to the topic. Were found 996 total publications, 248 publications were highlighted and 04 selected works, for answer the research objective. It can be stated that of selected publications, 100% is national. It’s also noticed that, as for the years of publication, the works are distributes equally within the five years established as inclusion criteria. In addition, as the database, all were indexed to LILACS. The articles were grouped into 3 thematic categories: The residency in obstetric nursing, The training of pregnant women during prenatal care and The obstetric nurse inserted in prenatal care. It is evidente that there were few studies focused specifically on this topic. The selected articles portray that the topic: Training for Childbirth Education is little explored in the scientific literature.